The Role of School Libraries in Supporting Distance Education: A Narrative Review: Peran Perpustakaan Sekolah dalam Mendukung Pendidikan Jarak Jauh: Sebuah Tinjauan Naratif - Dwi Fajriyah, Annisa; Rully Khairul Anwar; Siti Chaerani Djen Amar; Evi Nursanti Rukmana (Universitas Airlangga, 2025)
Background: Library are one of the important supporting factors in the world of education, both direct education and distance education because they play a role in providing learning resources. School libraries in distance education have roles that must be implemented and maximized so that the continuity of learning does not become difficult. Purpose: This research focuses on the purpose of knowing the role of school libraries in supporting distance education through the analysis of providing access to learning resources, increasing students' literacy interest, and providing digital services. Method: This research uses a narrative literature review method from references related to the topic of the role of school libraries in supporting distance education with the number of main references analyzed as many as six references. Findings: The results show that school libraries have an important role to play in supporting distance education. School libraries need to provide digital learning resources to sustain distance education. In addition, the library plays a role in increasing students' literacy interest through interactive programs and online discussion tools. Services in school libraries also need to be adapted to digital services that can be accessed anytime by learners. Conclusion: School libraries play a crucial role in distance education by providing access to digital learning resources, improving learner literacy, and providing digital services that facilitate the learning process. Future research could focus on the development of inclusive digital infrastructure, collaboration with online platforms, and access solutions in remote areas for education equity. ————————————————————————————————————————————————————————————– ABSTRAK Peran Perpustakaan Sekolah dalam Mendukung Pendidikan Jarak Jauh: Sebuah Tinjauan Naratif Latar Belakang: Perpustakaan menjadi salah satu faktor penunjang penting dalam dunia pendidikan, baik pendidikan langsung maupun pendidikan jarak jauh karena berperan dalam pengadaan sumber belajar. Perpustakaan sekolah dalam pendidikan jarak jauh memiliki peran-peran yang harus dilaksanakan dan dimaksimalkan agar keberlangsungan pembelajaran tidak menjadi sulit. Tujuan: Penelitian ini bertujuan untuk mengetahui peran perpustakaan sekolah dalam mendukung pendidikan jarak jauh melalui analisis penyediaan akses sumber belajar, peningkatan minat literasi peserta didik, dan penyediaan layanan digital. Metode: Penelitian ini menggunakan metode narrative literature review dari rujukan yang berkaitan dengan topik peran perpustakaan sekolah dalam mendukung pendidikan jarak jauh dengan jumlah rujukan utama yang dianalisis sebanyak enam rujukan. Temuan: Hasil penelitian menunjukkan bahwa perpustakaan sekolah memiliki peran penting untuk mendukung pendidikan jarak jauh. Perpustakaan sekolah perlu menyediakan sumber belajar digital untuk keberlangsungan pendidikan jarak jauh. Selain itu, perpustakaan ikut berperan dalam meningkatkan minat literasi peserta didik melalui program interaktif dan sarana diskusi online. Layanan di perpustakaan sekolah juga perlu diadaptasikan menjadi layanan digital yang dapat diakses kapan saja oleh peserta didik. Kesimpulan: Perpustakaan sekolah memiliki peran krusial dalam pendidikan jarak jauh melalui penyediaan akses sumber belajar digital, peningkatan literasi peserta didik, dan penyediaan layanan digital yang mempermudah proses pembelajaran. Penelitian selanjutnya dapat berfokus pada pengembangan infrastruktur digital yang inklusif, kolaborasi dengan platform daring, serta solusi akses di daerah terpencil untuk pemerataan pendidikan. Kata Kunci: Perpustakaan Sekolah; Pendidikan Jarak Jauh; Perpustakaan Digital